Therapeutic Applications of Plant Virus Nanoparticles in Cancer Treatment and Nanomedicine - Majid, Muhammad; Hussain, Mansor; Khaliq, Hamza; Abbas, Usman; Tariq, Roha; Abdul Qayoom (Indus Journal of Bioscience Research, 2025)
Plant virus nanoparticles (VNPs) are inexpensive to produce, dependable, and reusable and have emerged as a versatile and promising platform in nanomedicine, particularly cancer therapy. These biogenic nanostructures possess unique physicochemical properties, including biocompatibility, biodegradability, and structural uniformity, making them ideal candidates for targeted drug delivery. The ability of such nanoparticles to encapsulate chemotherapeutic agents and functionalize with tumor-specific ligands facilitates precise delivery to cancerous tissues, minimizing off-target effects and enhancing therapeutic efficacy. In addition, plant viral vectors (VLPs) are an attractive option for causing anti-tumor immunity because they are undoubtedly secure, harmless, and suitable for mass manufacture and pharmacological adaptation. This review delves into the molecular architecture of plant virus nanoparticles, their functional modifications, and the mechanisms by which they interact with cancer cells. Additionally, it highlights preclinical studies and emerging clinical applications, addressing both the opportunities and challenges in translating VNPs from bench to bedside. By exploring the anticancer potentials of VNPs, this paper aims to underscore their role in shaping the future of sustainable, plant-derived nanotechnology for oncology.